2002
DOI: 10.1634/stemcells.20-5-428
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Progenitor Cells Derived from Embryonic Stem Cells: Analysis of Gene Expression

Abstract: Rhesus monkey embryonic stem (ES) cells undergo differentiation in vitro towere obtained with the latter system, suggesting that this variation may be species specific. We observed, however, that CD34 + and CD34 + CD38 -cells derived from ES cells expressed embryonic ε and ζ as well as α, β, and γ globin genes, whereas no expression of embryonic globins could be detected in the cell preparations from BM. Moreover, erythroblast-enriched CD34 -cells derived from 4-or 5-week ES cell differentiation cultures also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…In this regard, dedifferentiated structures have also been implicated as developmentally plastic transitional structures that serve to direct cell expansion and tissue differentiation in numerous species 71,72 including humans. 73 In keeping with these previous findings, the switch from islet to DEC is associated with upregulated expression of markers associated with stemness [48][49][50][51][52] including CD34, ABCG2, a-fetoprotein, b-galactosidase, PYY, nestin and NGN-3. Stocum has introduced the concept of regeneration competence 46 to describe adult cells that can be induced to regenerate the body's own tissues.…”
Section: Discussionsupporting
confidence: 78%
“…In this regard, dedifferentiated structures have also been implicated as developmentally plastic transitional structures that serve to direct cell expansion and tissue differentiation in numerous species 71,72 including humans. 73 In keeping with these previous findings, the switch from islet to DEC is associated with upregulated expression of markers associated with stemness [48][49][50][51][52] including CD34, ABCG2, a-fetoprotein, b-galactosidase, PYY, nestin and NGN-3. Stocum has introduced the concept of regeneration competence 46 to describe adult cells that can be induced to regenerate the body's own tissues.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, in vitro and in vivo studies of primate hematopoietic development should be performed using primate-derived materials. In recent studies in primate ES cells, Kaufman et al and Li et al the coexistence of primitive and definitive hematopoiesis is recapitulated at the mRNA level (Lu et al, 2002). In this study, we have demonstrated for the first time the transition from primitive to definitive hematopoietic development in primate ES cells at both the transcriptional and the translational level in vitro.…”
Section: Discussionsupporting
confidence: 65%
“…Therefore, their ES cells might be used as a model for elucidating primate hematopoietic development. Recently primate ES cell lines were established (Thomson et al, 1995;Thomson et al, 1996;Thomson et al, 1998;Suemori et al, 2001), and hematopoietic differentiation from primate ES cells was also induced successfully in vitro (Kaufman et al, 2001;Li et al, 2001;Lu et al, 2002;Chadwick et al, 2003). However, compared with the murine system, little work has been done to precisely analyze primitive and definitive hematopoietic development.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on in vitro differentiating mouse ESCs have shown that erythropoietic differentiation within EBs recapitulates the transition from the primitive to the definitive lineages, 42,43 as defined by a switch from embryonic () to adult (␤) globin expression, respectively. To further characterize the erythroid subsets emerging from both control and VEGF-A 165 -treated EBs in the human, we assessed the transcriptional status of the embryonic and adult globin genes.…”
Section: Vegf-a 165 Enhances the Expression Of Both The Embryonic Andmentioning
confidence: 99%